Occupational prestige, social mobility and the association with lung cancer in men. Issue 1 (December 2016) - Behrens, Thomas; Groß, Isabelle; Siemiatycki, Jack; Conway, David; Olsson, Ann; Stücker, Isabelle; Guida, Florence; Jöckel, Karl-Heinz; Pohlabeln, Hermann; Ahrens, Wolfgang; Brüske, Irene; Wichmann, Heinz-Erich; et al.
Abstract Background The nature of the association between occupational social prestige, social mobility, and risk of lung cancer remains uncertain. Using data from the international pooled SYNERGY case–control study, we studied the association between lung cancer and the level of time-weighted average occupational social prestige as well as its lifetime trajectory. Methods We included 11, 433 male cases and 14, 147 male control subjects. Each job was translated into an occupational social prestige score by applying Treiman's Standard International Occupational Prestige Scale (SIOPS). SIOPS scores were categorized as low, medium, and high prestige (reference). We calculated odds ratios (OR) with 95 % confidence intervals (CI), adjusting for study center, age, smoking, ever employment in a job with known lung carcinogen exposure, and education. Trajectories in SIOPS categories from first to last and first to longest job were defined as consistent, downward, or upward. We conducted several subgroup and sensitivity analyses to assess the robustness of our results. Results We observed increased lung cancer risk estimates for men with medium (OR = 1.23; 95 % CI 1.13–1.33) and low occupational prestige (OR = 1.44; 95 % CI 1.32–1.57). Although adjustment for smoking and education reduced the associations between occupational prestige and lung cancer, they did not explain the association entirely. Traditional occupational exposures reduced the associations only slightly. We observed small associations with downward prestige trajectories, with ORs of 1.13, 95 % CI 0.88–1.46 for high to low, and 1.24; 95 % CI 1.08–1.41 for medium to low trajectories. Conclusions Our results indicate that occupational prestige is independently associated with lung cancer among men.